PENDIDIKAN DALAM KONSEP ISLAM - Syafrida Siregar, Lis Yulianti (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
Abstract: Islam is a religion, and is also as a system of culture which gives sign that education is important. The purpose of education is not permanent and static. The purpose of education in globally are to make personality of someone become a good person or in Islam is said InsanKamil. The characteristic of InsanKamil is change of attitude and behavior suitable with indication of Islam. Education of Islam is there as long as life in the earth, so the last purpose of education is found in the life until the end of the life.Keywords: Islam, Education, Attitude and Behavior Â Abstrak: Islam adalah suatu agama, dan juga sebagai sebuah sistem budaya yang memberi tanda bahwa pendidikan itu penting. Tujuan pendidikan tidak bersifat tetap dan statis. Tujuan pendidikan di seluruh dunia yang membuat kepribadian seseorang menjadi orang yang baik atau dalam Islam dikatakan Insan Kamil. Karakteristik Insan Kamil adalah perubahan sikap dan perilaku yang sesuai dengan indikasi Islam. Pendidikan Islam yang ada selama hidup di bumi, sehingga tujuan terakhir dari pendidikan ditemukan dalam kehidupan sampai akhir hidup.Â Kata Kunci: Islam, Pendidikan, Sikap dan Perilaku